Marketing de relacionamento aplicado a redes de cooperação: os casos Mania Sul e Construmais - Mello Filho, Luiz Leandro de (2007)
In the present study, relationship marketing actions have been approached from the symbiosis of the models described by Vavra (1993) and Souza (1997) in two groups of small retail sale companies together in a cooperation net. The nets 'Construmais' and 'Mania Sul", which work as a construction material store and a supermarket store, respectively, have been studied. These nets are composed of several small enterprises located in the central region of Rio Grande do Sul state and, have been created through a partnership between UFSM (Federal University of Santa Maria) and SEDAI/RS. It is named Program of Cooperation Nets. The study method was a multicase one, which made possible to analyse the above mentioned nets without worrying about comparing them. The research has been shared by the owners, the internal clients and the external clients. For the owners, a specific questionnaire answered by all owners has been used. Thew added up to 18 ones for 'Construmais' and 8 ones for 'Mania Sul'. For the internal and external clients two types of questionnaires have been used. They were structured in accordance with the scale 'Likert' and it used as a sample 71 and 84 internal clients and 393 and 383 external clients for 'Construmais' and for 'Mania Sul', respectively. This sample indication has been done considering an infinite population with a sample mistake of 3% counted by the 'Statistical Analysis System'. The results point out the increasing of sales in all stores of both nets, having as positive factors: better store windows, reduction of prices, the use of standardized uniforms of their employees and a better and faster service. Thus, it can be concluded that the model of cooperation nets is a favourable method for the small and medium businessmen who are able to become more competitive locally through actions of marketing on a collective and structured relationship, through the scale economy used in this sort of organizational group as it has been seen in these studied nets